► Trading proposal to promote the export of native colored cotton blankets from the CITE Sipan to the Germany market, 2020 - Diaz Caro, Frank (2020)
The objective is to generate a marketing proposal that encourages the export of colored native cottonblankets made by CITE SIPAN artisans to the German market. The hypothetical-deductive method wasused and the results indicated that the artisans of the CITE-SIPAN expect to be able to export theirproducts but require follow-up due to the lack of knowledge of the tools necessary for export, whilemarket research indicates that according to the In charge of retail in the city of Hamburg, Peruviannative cotton blankets will have acceptance and may be distributed if the minimum requirements aremet. It was determined that the marketing proposal must meet the requirements of the German marketin the area of promotion and distribution if it encourages artisans to export blankets made of colorednative cotton.